Development of Cellular and Enzymatic Bioluminescent Assay Systems to Study Low-Dose Effects of Thorium; Bioengineering; Vol. 8, iss. 12 - Kolesnik O. V. Olga; Rozhko T. V. Tatjyana Vladimirovna; Lapina M. A. Mariya; Solovjyov V. S. Vladislav Sergeevich; Sachkova A. S. Anna Sergeevna; Kudryasheva N. S. Nadezhda Stepanovna (2021, 2021)
Title screen